2015
DOI: 10.1007/s00223-015-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Bone Strength is Enhanced in the Jump Leg of Collegiate-Level Jumping Athletes: A Within-Subject Controlled Cross-Sectional Study

Abstract: An efficient method of studying skeletal adaptation to mechanical loading is to assess side-to-side differences (i.e. asymmetry) within individuals who unilaterally exercise one side of the body. Within-subject controlled study designs have been used to explore skeletal mechanoadaptation at upper extremity sites; however, there is no established model in the lower extremities. The current study assessed tibial diaphysis and distal tibia asymmetry in collegiate-level jumping athletes (N = 12). To account for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…Cheng et al [1] found that 12 months' hormone replacement therapy (HRT) and HRT combined with high-impact training mostly increased proximal tibia BMC in the A-P direction, resulting in increased bending resistance at the maximum axis (Imax). Similarly, in previous observational studies comparing athletes and reference subjects [8,9], active and inactive monozygotic and dizygotic twins [10] or the jump and lead leg of jumping athletes [35], bone mass was greater in the A-P direction, as indicated by higher Imax. In the present study, adaptation in that direction might have already reached its maximum owing to the long-term training history of the athletes, as the intervention-related increase in bending resistance was observed largely at the minimum axis (IminA).…”
Section: Discussionsupporting
confidence: 58%
“…Cheng et al [1] found that 12 months' hormone replacement therapy (HRT) and HRT combined with high-impact training mostly increased proximal tibia BMC in the A-P direction, resulting in increased bending resistance at the maximum axis (Imax). Similarly, in previous observational studies comparing athletes and reference subjects [8,9], active and inactive monozygotic and dizygotic twins [10] or the jump and lead leg of jumping athletes [35], bone mass was greater in the A-P direction, as indicated by higher Imax. In the present study, adaptation in that direction might have already reached its maximum owing to the long-term training history of the athletes, as the intervention-related increase in bending resistance was observed largely at the minimum axis (IminA).…”
Section: Discussionsupporting
confidence: 58%
“…The different mechanisms through which bone mass and safety factors are balanced within the limb are consistent enough that a pattern has emerged in the literature across various species, by which mechanical strain is accommodated through enhanced internal trabecular bone structure in epiphyses, and through enhanced external size and strength in diaphyseal regions (Barak, Lieberman, & Hublin, ; Kivell, ; Matarazzo, ; Mittra, Rubin, & Qin, ; Polk, Blumenfeld, & Ahluwalia, ; Pontzer et al, ; Ryan & Shaw, ; Welch, ). This pattern is also consistently documented among living human athletes (Ducher, Prouteau, Courteix, & Benhamou, ; Hart et al, ; Heinonen et al, ; Heinonen, Sievänen, Kannus, Oja, & Vuori, ; Ireland et al, ; Izard et al, ; Kontulainen, Sievänen, Kannus, Pasanen, & Vuori, ; Nikander, Sievänen, Uusi‐Rasi, Heinonen, & Kannus, ; Weatherholt & Warden, ). However, evidence of this pattern in the lower limb bones among living humans has been established predominantly from the tibia, extending occasional to the distal femoral epiphysis.…”
supporting
confidence: 56%
“…Biomechanical analyses in bioarchaeology and paleoanthropology frequently seek to infer human behavior in the past from between‐group differences in limb bone cross‐sectional geometric (CSG) properties, reflecting both diaphyseal areas and the radial distribution of bone (Macintosh, Davies, Pinhasi, & Stock, ; Macintosh, Pinhasi, & Stock, ; Macintosh, Pinhasi, & Stock, ; Ruff et al, ). The conclusions drawn are based upon relationships between cortical bone area and compressive strength, and between cortical bone distribution and bending/torsional rigidity (Ruff, ) that are supported by the clinical literature (Hart et al, ; Hind, Gannon, Whatley, Cooke, & Truscott, ; Izard, Fraser, Negus, Sale, & Greeves, ; Nikander et al, ; Rantalainen, Nikander, Daly, Heinonen, & Sievänen, ; Rantalainen, Nikander, Heinonen, Suominen, & Sievänen, ; Weatherholt & Warden, ). Similarly, evidence of trabecular bone variation in response to loading among living athletes (Best, Holt, Troy, & Hamill, ; Heinonen, Sievänen, Kyröläinen, Perttunen, & Kannus, ; Modlesky, Majumdar, & Dudley, ; Schipilow, Macdonald, Liphardt, Kan, & Boyd, ), in combination with modern imaging methods, has begun to enable the study of complex three‐dimensional structural changes in epiphyseal trabecular bone from a locomotor perspective (Chirchir, Ruff, Junno, & Potts, ; Chirchir, Zeininger, Nakatsukasa, Ketcham, & Richmond, ; Matarazzo, ; Ryan & Shaw, ; Saers, Cazorla‐Bak, Shaw, Stock, & Ryan, ; Shaw & Ryan, ; Tsegai et al, ).…”
mentioning
confidence: 94%
“…This is the first known study to assess bilateral differences in the bone characteristics of speed skaters, but previous studies have shown differences in the bone characteristics when assessing bilateral sports. The racket arm of tennis players was shown to have greater BMC and cross sectional area in comparison to the non-racket arm [2], while the cortical area and cortical thickness at the 66% site of the tibia were higher in the take-off of leg compared to the non-take-off leg in collegiate long jumpers [27] .…”
Section: Discussionmentioning
confidence: 82%